Subjective Perception of Discomfort due to Vehicle Vibrations in the Sagittal Plane. Issue 19 (2016) - Mulder, Mark; Abbink, David A.
Abstract: Over many years the current state-of-the-art of passive suspension systems have greatly improved driver and passenger ride-comfort. With the advent of active suspension systems, the possibilities for even more fine-tuned ride comfort have increased significantly. Pushing the performance of the active suspension systems beyond the existing ride comfort, however, requires a deeper understanding of how humans physically react to vehicle perturbations. We conducted a perturbation experiment to determine how vibration perturbation characteristics in the sagittal plane - that is, the longitudinal, vertical and pitch directions - were related to subjectively perceived levels of discomfort. We expected that there would be a combination of amplitude and frequency at which maximal discomfort (inverted 'U-shape') is experienced. The results of the experiment confirmed our hypothesis. More specifically, discomfort increased with increasing amplitude of the vibration perturbation and with increased bandwidth of the vibration perturbation. Furthermore, we found that there is a strong interaction effect between bandwidth and amplitude. Hence, for large amplitude vibrations it is important to limit the bandwidth of the frequency content, while for high bandwidth vibrations it is important to limit the amplitude.